Minimizing Information Asymmetry Interference in Multi-radio Multi-channel Wireless Mesh Networks - Sadiq Shah; Arbab Waseem Abbas; Hameed Hussain; Huma Israr (Kuwait Journal of Science)
Multi-radio multi-channel wireless mesh networks in recent years have become a preferredchoice for end users as they are reliable and extend the network connectivity on the last mile.MRMC-WMNs have already been deployed at various locations but still wireless mesh networkfaces link interference issues i.e. information asymmetry, near-hidden and far-hidden terminals.Information asymmetry interference is one of the major problems that degrade the capacity ofmulti-radio multi-channel wireless mesh network. To maximize the multi-radio multi-channelwireless mesh network capacity in this paper we are presenting an algebraic channel assignmentmodel that minimizes information asymmetry interference. Our proposed model optimallyassigns IEEE 802.11b/g non-overlapping channels to various links of multi-radio multi-channelwireless mesh network. The optimal channel assignment model also maximizes the overallcapacity of the multi-radio multi-channel mesh network. For extensive simulations we considermultiple wireless mesh network scenarios. We compare the results of both the scenarios whereour algebraic optimization model has been applied with those where the model has not beenapplied. Simulation results show that our proposed optimization model maximizes the capacityof multi-radio multi-channel wireless mesh networks up to 8%.